Regional Variations in Agricultural Productivity- A Study of Uzbekistan - Zahoor ul Hassan2*, M. Maqbool Bhat1, M. Imran Malik2 (Journal of Phytology, 2011)
Agriculture plays an important role in Uzbekistan’s economy. It provides employment to about 60 percent rural population. The agricultural sector accounts for 12.2 percent of production assets, 44.4 percent of employment, 70 percent trade, 30.1 percent of G.D.P and 60 percent of exports. The aim of this work is to analyse the temporal and spatial variation in agricultural productivity. This was achieved by employing spearman’s rank correlation to the agricultural productivity of the thirteen states of Uzbekistan. The study has revealed that the agricultural productivity has shown marked regional variations. The study area has been divided into five regions on the basis of agricultural productivity. The highest productivity region consists of the states of Fargana and Sirdarya while the lowest productivity region consists of the states of Karakalpakstan and Bukhara. The disparity can be solved through increased output, both in surplus, marginal and negative areas of crop production.